APLIKASI LOCATION BASED ADVERTISING DENGAN METODE PUSH DAN PULL PADA SISTEM OPERASI ANDROID - , REDHA JAUHAR RAHMADY, Sigit Priyanta, S.Si, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta is one of the major cities that frequently visited by many tourists, both local and foreign. Both of them are sometimes difficult to find something that is needed. With Location Based Service (LBS) technology it will be much easier, especially in terms of getting information about advertisement or often called as Location Based Advertising (LBA). In LBA there are two ways to provide information that is by the push and pull method that allows users to get information precisely from the time period and place. This research will build an location based advertising application on Android devices that can provide information about advertisement in the notification when the user enters a certain radius and can do a search of public facilities location service such as search of goods, ATM, hospital, gas station, restaurant and hotel The results show that the application can provide an advertisement information when the user is less than 500 meters from the location of the shopping center, showing the location of the user, showing the search results of public facilities service based on userâs input and shows the route to the intended location.